2008
DOI: 10.1007/s11605-008-0625-5
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient Mortality Analysis of Paraesophageal Hernia Repair in Octogenarians

Abstract: Non-elective repair was associated with a six to sevenfold increase in mortality and longer length of stay. Earlier elective repair of paraesophageal hernia may reduce mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 13 publications
2
39
0
1
Order By: Relevance
“…Using US Nationwide Inpatient Sample data for 2005, Poulose et al [7] compared emergent and elective Multivariate logistic regression with model selection Cost data further support elective repair in that costs were higher for emergent admissions compared to elective ones. Total charges were also higher in patients with emergent operative admissions compared to elective operative admissions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using US Nationwide Inpatient Sample data for 2005, Poulose et al [7] compared emergent and elective Multivariate logistic regression with model selection Cost data further support elective repair in that costs were higher for emergent admissions compared to elective ones. Total charges were also higher in patients with emergent operative admissions compared to elective operative admissions.…”
Section: Discussionmentioning
confidence: 99%
“…3) or diaphragmatic hernia with obstruction (552.3) were selected. The selected codes are commonly used for paraesophageal hernia and intrathoracic stomach and have been used by other investigators [6,7]. Data were limited to principal diagnosis codes 552.3 and 553.3 on individuals 18 years or older and excluded principal diagnosis codes that do not accurately reflect intrathoracic stomach, including codes for gastroesophageal reflux (530.81), congenital hernias (750.6, 756.6), or traumatic hernias (862.0, 862.1).…”
Section: Study Populationmentioning
confidence: 99%
“…Recent large scale population analyses have suggested that mortality of emergent paraesophageal hernia repair is high relative to elective repair. 5,6 As such, the timing of repair remains controversial, particularly the relative benefit of watchful waiting vs. early elective repair and the risk of emergent repair. The aim of the study was to assess the perioperative clinical outcomes and compare the morbidity and mortality of elective and acute repair of patients with an intrathoracic stomach.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in results among these studies may be related to the definition threshold for advanced age. In this study, a threshold age of 60 years was used, while some study used 70 years [9], and others used 80 years [7,13,26]. Our finding of an association between annual case volume and outcome does bring into question any need for regionalization of care to high-volume hospitals.…”
Section: Discussionmentioning
confidence: 90%
“…However, the association between advanced age and higher mortality after laparoscopic paraesophageal hernia repair is conflicting in the literature. Larusson et al [9] reported an association of increased mortality with advanced age but other studies did not find this association [7,13,26]. Differences in results among these studies may be related to the definition threshold for advanced age.…”
Section: Discussionmentioning
confidence: 92%